IMPLEMENTASI PENDIDIKAN INKLUSIF SEBAGAI PERUBAHAN PARADIGMA PENDIDIKAN DI INDONESIA - Irvan, Mochamad; Jauhari, Muhammad Nurrohman (Buana Pendidikan, 2018)
The aim of implementing Inclusive education is providing opportunities for all students to fulfill the right of children with disabilities that is to learn together with other students in a school environment. The implementation of inclusive schools should initiate an inclusive culture, and a friendly environment for children with disabilities. The writing of this article aims to examine the implementation of inclusive education in Indonesia. The data are processed, obtained through literature study, interview, and field observation. Data collected are analyzed using qualitative approach. The data obtained shows that the implementation of inclusive school has not been evenly distributed in every region, not have adequate accessibility yet, and not fulfillment of competent educator in special education field yet. Based on the analysis it can be concluded that the implementation of inclusive education requires the function of supervision, assistance, and evaluation to support the positive progress of inclusive education in terms of both quantity and quality.